Optimization of the Performance of Crime Investigation Unit of the Subregional Police of Sukoharjo in the Investigation of Vehicle Theft Criminal Acts for the Realization of Law Enforcment According to Precision - Alif Hilmy Maulana (Advances in Police Science Research Journal, 2022)
The writing of this final task was motivated by the crime of vehicle theft in the jurisdiction of the Sukoharjo Subregional Police for the past five years. By prioritizing repressive methods, the Criminal Investigation Unit in carrying out repressive efforts to vehicle theft criminal acts in the Sukoharjo Subregional Police By conducting investigation and investigation activities so that the vehicle theft case can be revealed and handed over to the Public Prosecutor for trial. The purpose of this writing is to find out how to optimize the performance of Crime Investigation Unit in Subregional Police of Sukoharjo in the investigation of vehicle theft criminal acts for the realization of law enforcment according to precision. As an analysis knife, the author uses several theories and concepts, namely: optimization theory, competency theory, performance concept, management theory, criminal investigation unit concept, investigation concept, vehicle theft concept and law enforcement concept. With the research area in Sukoharjo Subregional Police. This research is carried out with a qualitative approach, using field research types, as well as data collection techniques with observation, interviews, and document studies. The location of the research is in Sukoharjo Regency. The results of the study found that there were several problems in the implementation of performance optimization, where there were found factors that influenced the knowledge, skills and attitude of crime invetigation unit members of the Sukoharjo Subregional Police. There were also several problems mainly in the crime investigation unit performance of the Sukoharjo Subregional Police where the author analyzed using management theory in terms of Man, Money, Materials and Methods and in optimizing the performance of Crime Investigation Unit of the Subregional Police of Sukoharjo, the author conducted an analysis using management theory in the form of planning, organizing, actuating and controlling. Based on research conducted by the author, it was found that the performance of the investigators has not worked optimally so that the number of cases of motor vehicle theft has not been resolved.